Kolaborasi Orang Tua dan Guru Akidah Akhlak dalam Meningkatkan Prestasi Siswa di Madrasah Aliyah Swasta Muallimin UNIVA Medan - Indra Laksana; Bahtiar Siregar (Islam & Contemporary Issues, 2025)
Collaboration between parents and teachers plays a crucial role in improving student achievement. This study aims to describe the forms of collaboration between Akidah Akhlak teachers and parents in improving student achievement, identify supporting and inhibiting factors, and analyze its influence on student achievement at the Muallimin UNIVA Medan Private Islamic Senior High School. This research contributes to previous studies by specifically highlighting the role of Akidah Akhlak teacher–parent collaboration in shaping both academic performance and students’ moral behavior within an Islamic educational context. Using a descriptive qualitative method, the study involved teachers, parents, and school administrators, with data analyzed using the Miles and Huberman interactive analysis model, including data reduction, data display, and conclusion drawing. The results showed that collaboration was actively carried out through routine communication, joint religious activities, and coordinated moral development practices at home and school. Supporting factors included effective communication, shared awareness of the importance of moral education, and supportive school policies, while obstacles consisted of parents’ busy schedules and differences in parenting styles. This harmonious collaboration positively impacted academic achievement and non-academic outcomes, evidenced by increased student discipline, responsibility, and consistent religious behavior.